Pengaruh Quiet Quitting, Job Satisfaction dan Job Engagement Terhadap Employee Performance dengan Mediasi Turnover Intention Karyawan Gen Z pada Perusahaan Jasa di Kabupaten Sumenep - Nurcholis Setiawan; Mareta Putri Ayu Sartika (Indo Publishing, 2026)
This study aims to analyze the influence of quiet quitting, job satisfaction, and job engagement on employee performance, with turnover intention as a mediating variable among Gen Z employees in service companies in Sumenep Regency. As generation Z enters the workforce, their unique characteristics potentially affect organizational dynamics, including a tendency toward quiet quitting and high turnover intention due to job dissatisfaction. This research employs a quantitative approach using Structural Equation Modeling - Partial Least Square (SEM-PLS). Data were collected through questionnaires distributed to Gen Z employees in the service sector of Sumenep Regency. The results show that quiet quitting has a negative and significant impact on employee performance and a positive influence on turnover intention. Job satisfaction and job engagement negatively affect turnover intention, while Job Engagement positively impacts employee performance. Furthermore, turnover intention is proven to mediate the relationship between job satisfaction and employee performance. The implications of this study suggest that companies need to manage psychological factors influencing employee performance, including creating a supportive work environment that enhances engagement and job satisfaction to reduce quiet quitting and minimize turnover rates.